Transcriptomic analysis reveals the possible roles of sugar metabolism and export for positive mycorrhizal growth responses in soybean. Issue 3 (25th November 2018) - Zhao, Shaopeng; Chen, A.; Chen, Chengjie; Li, Chengchen; Xia, Rui; Wang, Xiurong
Abstract : To elucidate molecular mechanisms controlling differential growth responses to root colonization by arbuscular mycorrhizal (AM) fungi varying in colonization and cooperative behavior, a pot experiment was carried out using two soybean genotypes and three AM inocula. The results showed that inoculation by cooperative Rhizophagus irregularis (Ri) or less cooperative Glomus aggregatum with high AM colonization (Ga‐H) significantly promoted plant growth compared with inoculation by G. aggregatum with low AM colonization (Ga‐L). A comparative RNA sequencing analysis of the root transcriptomes showed that fatty acid synthesis pathway was significantly enriched in all three AM inoculation roots. However, sugar metabolism and transport were significantly enriched only in Ri and Ga‐H inoculation, which was consistent with positive growth responses in these two inoculation treatments. Accordingly, the expression levels of the key genes related to sugar metabolism and transport were also upregulated in Ri and Ga‐H roots compared with Ga‐L roots. Of them, two sugars will eventually be exported transporters ( SWEET ) transporter genes, GmSWEET6 (Glyma.04G198600) and GmSWEET15 (Glyma.06G166800), and one invertase (Glyma.17G227900) gene were exclusively induced only in Ri and Ga‐H roots. Promoter analyses in transgenic soybean roots further demonstrated that GUS driven by the GmSWEET6 promoter was highly expressed in arbuscule‐containing cortical cells. Additionally, Ri and Ga‐H inoculation increased the contents of sucrose, glucose and fructose in both shoots and roots compared with those of Ga‐L and non‐mycorrhizal. These results imply that positive mycorrhizal growth responses in plants might mostly be due to the stimulation of photosynthate metabolism and transport by AM fungal inoculum with high colonization capabilities.